Does Corporate Ownership matter for Firm Performance? Evidence from Chinese Stock Exchanges - Rathnayake, Dilesha Nawadali; Kassi, Diby Francois; Louembe, Pierre Axel; Sun, Gang; Ning, Ding (International Journal of Economics and Financial Issues, 2019)
This paper examines the impact of corporate ownership structure and ownership concentration on the corporate performance of listed firms in China. Ordinary Least Square (OLS) and Two-Stages Least Squares (2SLS) models are used to capture the relationship between the independent variables and firm performance by considering the possible endogeneity of both performance and ownership variables. The ownership structure variables (executive shares, State shares, legal shares, and Negotiable A-shares) are negatively related with firm performance measured by Tobin’s Q ratio. The proportion of state-owned shares and negotiable A-shares are significantly correlated with the firm profitability. Second, the results show that Chinese firm ownership is severely concentrated. The top ten largest shareholders accounted for 60% of the outstanding shares in 2017 and had a strong positive relationship with firm performance. In contrast, the largest shareholder’s ownership concentration ratio variable has a significant negative relationship with the firm performance. Keywords: Ownership structure, Ownership concentration, firm performance, China, Endogeneity JEL Classifications: G1, G10, G18, G32 DOI: https://doi.org/10.32479/ijefi.7336